Genetic and virulence characteristics of hybrid Shiga toxin-producing and atypical enteropathogenic Escherichia coli strains isolated in South Korea - Lee, Woojung; Ha, Jina; Choi, Jaehyun; Jung, Yewon; Kim, Eiseul; An, Eun Sook; Kim, Seung Hwan; Shin, Hakdong; Ryu, Sangryeol; Kim, Soon Han; Kim, Hae-Yeong (Frontiers in Microbiology, 2024)
Introduction: The predominant hybrid pathogenic E. coli, enterohemorrhagic E. coli (EHEC), combines characteristics of Shiga toxin-producing E. coli (STEC) and enteropathogenic E. coli (EPEC), contributing to global outbreaks with severe symptoms including fatal consequences. Since EHEC infection was designated as a notifiable disease in 2000 in South Korea, around 2000 cases have been reported, averaging approximately 90 cases annually.Aim: In this work, genome-based characteristic analysis and cell-based assay of hybrid STEC/aEPEC strains isolated from livestock feces, animal source foods, and water in South Korea was performed.Methods: To identify the virulence and antimicrobial resistance genes, determining the phylogenetic position of hybrid STEC/aEPEC strains isolated in South Korea, a combination of real-time PCR and whole-genome sequencing (WGS) was used. Additionally, to assess the virulence of the hybrid strains and compare them with genomic characterization, we performed a cell cytotoxicity and invasion assays.Results: The hybrid STEC/aEPEC strains harbored stx and eae genes, encoding Shiga toxins and E. coli attachment/effacement related protein of STEC and EPEC, respectively. Furthermore, all hybrid strains harbored plasmid-carried enterohemolysin(ehxCABD), a key virulence factor in prevalent pathogenic E. coli infections, such as diarrheal disease and hemolytic-uremic syndrome (HUS). Genome-wide phylogenetic analysis revealed a close association between all hybrid strains and specific EPEC strains, suggesting the potential acquisition of Stx phages during STEC/aEPEC hybrid formation. Some hybrid strains showed cytotoxic activity against HeLa cells and invasive properties against epithelial cells. Notably, all STEC/aEPEC hybrids with sequence type (ST) 1034 (n=11) exhibited higher invasiveness than those with E2348/69. This highlights the importance of investigating potential correlations between STs and virulence characteristics of E. coli hybrid strains.Conclusion: Through genome-based characterization, we confirmed that the hybrid STEC/aEPEC strains are likely EPEC strains that have acquired STEC virulence genes via phage. Furthermore, our results emphasize the potential increased danger to humans posed by hybrid STEC/aEPEC strains isolated in South Korea, containing both stx and eaeA, compared to STEC or EPEC alone.